PERAN PENDAMPING DESA DALAM IMPLEMENTASI PROGRAM AIR BERSIH (PIPANISASI) MENUJUH KESEJAHTERAAN MASYARAKAT DI DESA WASALABOSE KECAMATAN KULISUSU KABUPATEN BUTON UTARA - Irma, Irma; Kasim, Syaifuddin S.; Tanzil, Tanzil (WELL-BEING: Journal of Social Welfare, 2022)
Village facililtators are tasked with overseeing development from then planning, implementation, and monitoring stages. The purpose of this study was to determine the role of village facilitators in the implementation of the clean water program (pipanization) towards community welfare and to dertermine the factors that support and hinder the role of village assistants in the implementation of the clean water program (pipanization) towards community welfare in the village of wasalabose, kulisusu District north button. This research method is descriptive qualitative. The informants in this study were village assistants, wasalabose village head, village secretary, field workers and the community. The results of this study indicate that first, the role of village assistants in the implementation of the clean water frogram (pipanization) namely planning, implementation, utilization, and maintenance. Second, the supporting factor of this clean water program is the existence of adequate resources, which is certainly very helpful in implementing the program so that it runs well. The availability of resources, community participation and cooperation. Third, the inhibiting factors of the clean water program are the quality and quantity of water, as well as budgeting. The existence of a rule or policy made by the government is an effort to build and achieve prosperity. To achieve this walfare the policy must be implemented as well as possible.